Islam Berkemajuan Perspektif Najib Burhani - Ismasnawati; Karim Elhusein, Sofwan; Lahmi, Ahmad; Asmaret, Desi; Dahlan, Dasrizal (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This research aims to discuss Progressive Islam from Najib Burhani's perspective. The approach in this research is to use a literature study approach with a qualitative method. The results of his research, namely, Najib Burhani includes concepts and thoughts about how Islam can adapt and develop along with changing times. In this perspective, Najib Burhani outlined several main principles that teach Islamic teachings with social, economic and technological progress. He invited Muslims not only to view Islam as a rigid doctrine but also as a dynamic system that is able to provide solutions to various current problems. In this work, Najib Burhani emphasizes the importance of education, intelligence and innovation in creating a progressive Muslim society. He also reviewed the role of religious institutions in ensuring proper understanding of Islamic teachings in a modern context. Thus, it is hoped that "Progressing Islam" can become a guide for Muslims to integrate Islamic values ​​with worldly progress without sacrificing their original teachings and principles.